Integrated big data innovation in tourism management through the Pesona Karanganyar platform, Central Java - Sujatmiko, Sujatmiko; Huda, Muhammad Nurul; Qoyimah, Dinul (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2025)
The article examines the potential of big data application on the Pesona Karanganyar website to improve tourism management and boost tourism in Karanganyar Regency. The research uses Rogers' innovation attributes theory to address challenges faced by government managers and users in accessing information. The qualitative method includes website analysis, literature review, interviews, and data analysis using the interactive model. The results show that the website has a large, complex, and diverse data set that can meet information needs comprehensively. The website's innovations retain similarities without eliminating distinctive features. It adheres to simplicity, providing ease for users. The website's simple features make it easy for users to try out new features. Despite the extensive information, the website's ease of observation makes it easy for users to read and understand. However, challenges faced by the Karanganyar Regency Government in managing this website include technical errors such as signal disruptions and unexpected maintenance, which hinder users from accessing information and features on the website. To address this, continuous monitoring and evaluation of the Pesona Karanganyar platform are necessary to ensure technical reliability and service sustainability. This strategic step will not only optimize the user experience and enhance Karanganyar's tourism competitiveness but also provide a foundation for the development of a more robust and adaptive digital tourism management system in the future.